MANAJEMEN TENAGA PENDIDIK DAN KENDIDIKAN PERSPEKTIF AL-QUR’AN - Ansari, Adi (Universitas Islam Negeri Raden Intan Lampung, 2016)
This paper explores the meaning of the Qur'anverses that contain the concept of teachers andeducators employee management functions. Fromthis paper found that: First. The concept of planningare: (1) Al-Hashr: 18, that the man was told to planhis lunch for tomorrow; (2) Al-Baqarah: 197,concerning the obligation to plan carefully based onpiety to Allah. Second. Organizing concept containedin: (1) Al-Anfal: 46, about the importance of unity inall actions; (2) Ash-Shaff: 4, about the importance ofregularity; (3) Ali Imran: 159, on the order toapproach the meek and deliberation. Third. Theconcept of encouragement contained in Al-Kahf: 2,about the importance of the guidance process that isbased on religious principles. Fourth. The concept ofsupervision are: (1) Al-Mujadalah: 7, about themuraqobah; (2) Ash-Shaff: 2, absolute requirementfor leaders to be better than its members; (3) At-Tahrim: 6, about maintaining the safety.